2015
DOI: 10.1007/s11356-015-5297-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of PAH exposure and hematologic effects in subjects exposed to combustion emission during residential (and professional) cooking practices in Pakistan

Abstract: During the last decade, advances in analytical methods, an avalanche of information available over the Internet and a creation of international collaborations, have greatly increased our understanding of the role of trace elements in humans. Today, morbidity and mortality related to trace element deficiencies or toxicities affect more than half of the world's population. Research on both essential and toxic trace elements runs the gamut, from studies of dietary intake, requirements, and standards to optimal ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 88 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…Similar results were reported in another study among Indian women, where the women who used biomass fuels for cooking were found to have significantly higher levels of TNF-α, IL-6, IL-8, and CRP (Dutta et al, 2012). A study of Pakistani women reported higher mean serum concentrations of CRP among women cooking with biomass fuels in the home (1.9 mg/l) compared with non-exposed women (0.66 mg/l) (Kamal et al, 2016). However, a small pilot study among women in rural China found no differences in CRP levels between women with high versus low exposure to particulate matter with aerodynamic diameter < 2.5 μg (PM 2.5 ) (Shan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were reported in another study among Indian women, where the women who used biomass fuels for cooking were found to have significantly higher levels of TNF-α, IL-6, IL-8, and CRP (Dutta et al, 2012). A study of Pakistani women reported higher mean serum concentrations of CRP among women cooking with biomass fuels in the home (1.9 mg/l) compared with non-exposed women (0.66 mg/l) (Kamal et al, 2016). However, a small pilot study among women in rural China found no differences in CRP levels between women with high versus low exposure to particulate matter with aerodynamic diameter < 2.5 μg (PM 2.5 ) (Shan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies indicate that individuals exposed to biomass smoke have increased risk of respiratory symptoms and illnesses (Kurmi et al, 2013, Kurmi et al, 2010, Kamal et al, 2016, Regalado et al, 2006), including evidence of respiratory tract infections among individuals exposed to biomass smoke in Kenya (Ezzati and Kammen, 2001) and among South African children living in homes where polluting fuel sources are used for heating and cooking (Barnes et al, 2009). Studies also find more frequent respiratory symptoms or illness among women using traditional stoves compared to women using improved cookstoves (Clark et al, 2009, Romieu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the levels of eight urinary PAH metabolites as biomarkers of exposure to avoid the uncertainty of single biomarkers [49]. Effects on platelet counts have been recorded for PAHs generated during residential and professional cooking [50]. Our ndings suggest that PAH exposure (in particular PAHs that metabolize to 9hydroxy uorene) affects mean platelet volume, platelet distribution width, and platelet-large cell ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies did not assess the potential mechanism; thus the mechanism underlying the association remains largely unknown. Substantial previous studies showed that PAH exposure was associated with health damage by promoting the inflammation process, and PAH metabolites were associated with higher levels of C-reactive protein (CRP) [22,23]. In addition, as a biomarker of the inflammatory response, CRP was also reported to be involved in the process and occurrence of MetS [24].…”
Section: Introductionmentioning
confidence: 99%